2021
DOI: 10.2106/jbjs.rvw.21.00092
|View full text |Cite
|
Sign up to set email alerts
|

Long Head of the Biceps Tendon Ruptures

Abstract: » Pathology of the long head of the biceps tendon is a common source of shoulder pain and often occurs in combination with other shoulder disorders.» Nonsurgical management, including rest and activity modification, use of nonsteroidal anti-inflammatory drugs, physical therapy, and corticosteroid injections, is usually the first line of treatment.» Patients with symptoms that are refractory to nonsurgical management are indicated for biceps tenotomy or various tenodesis procedures.» Although several studies ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 58 publications
(142 reference statements)
0
2
0
1
Order By: Relevance
“…Sturzenegger et al [12] demonstrated that the strength of elbow flexion was diminished by 16%, that of supination of the forearm by 11%, and that of shoulder abduction by 16% following rupture of the LHBT. These findings indicate that some patients continue to have persistent biceps-related complications, such as cosmetic deformity, cramping, pain, and weakness [2,[5][6][7]13] and elect to undergo surgical intervention. When surgery is performed early enough after the injury, sufficient tendon remains to allow for tenodesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sturzenegger et al [12] demonstrated that the strength of elbow flexion was diminished by 16%, that of supination of the forearm by 11%, and that of shoulder abduction by 16% following rupture of the LHBT. These findings indicate that some patients continue to have persistent biceps-related complications, such as cosmetic deformity, cramping, pain, and weakness [2,[5][6][7]13] and elect to undergo surgical intervention. When surgery is performed early enough after the injury, sufficient tendon remains to allow for tenodesis.…”
Section: Discussionmentioning
confidence: 99%
“…
Long head of the biceps tendon (LHBT) ruptures are commonly seen in patients over the age of 50 years [1]. The anatomy of the tendon predisposes it to rupture as it courses through the bicipital groove prior to making a near 90° turn toward its attachment on the supraglenoid tubercle of the scapula and superior glenoid labrum [2]. Long head of biceps tendon tears are described as either partial-or full-thickness and often occur at the hypovascular zone between 1.2 and 3.0 cm from the origin of the tendon [3].
…”
mentioning
confidence: 99%
“… 12 Thus, pain relief from an injection may occur by treating other potential causes of anterior shoulder pain, including subacromial bursitis and rotator cuff-related pain. 1 Persistent groove pain following tenodesis used to be faulted to the suprapectoral technique. However, there is also increased awareness that biceps tenodesis, even when performed in the subpectoral region, does not always successfully resolve anterior shoulder pain that is often described as bicipital groove pain.…”
Section: Discussionmentioning
confidence: 99%
“…Tendinitis of the long head of the biceps brachii (LHB) tendon can be diagnosed arthroscopically by the presence of the "lipstick sign" (LS), as the tendon traverses within the bicipital groove over the anterosuperior humerus. 1 , 2 The hyperemic appearance of the so-called LS results from inflammatory tenosynovitis. 2 Although LHB tendinitis sometimes occurs in isolation, it is often present with a constellation of other shoulder pathologies, including rotator cuff tears or tendinosis, subacromial impingement, adhesive capsulitis, synovitis, labral tears, glenohumeral arthrosis, and acromioclavicular arthritis.…”
Section: Introductionmentioning
confidence: 99%
“…3% от всех повреждений сухожилия двуглавой мышцы плеча можно отнести к дистальным, что составляет от 2,55 до 5,35 клинических случая на 100 000 пациентов в год, преимущественно у мужчин 40-50 лет [1]. В основном это полнослойные и парциальные повреждения дистального сухожилия двуглавой мышцы плеча (ДСДМП) на доминирующей конечности (86%), приводящие к снижению сил супинации до 50% и сгибания в локтевом суставе до 30%, боли и мышечной деформации в виде обратного симптома «Popeye» [2].…”
unclassified